Changes in serotype distribution of Streptococcus pneumonia circulating among children in the Russian Federation after 13-valent pneumococcal conjugate vaccine introduction. - S. V. Sidorenko; Yu. V. Lobzin; W. Rennert; E. V. Nikitina; I. A. Tsvetkova; V. A. Ageevets; E. A. Martens; O. S. Kalinogorskaya; A. T. Ardysheva; L. T. Bayazitova; A. V. Bikmieva; E. V. Bolgarova; et al. (Журнал инфектологии, 2023)
During a prospective multicenter non-interventional observational study, a comparative assessment was made of the serotype structure of pneumococci circulating among healthy children under the age of 5 years and children of the same age group with signs of respiratory infections in the periods 2016-2018 and 2020-2022. Data on the serotype structure of pneumococci in the period from 2016-2018 were obtained from our previous works. In 2020-2022 the study included 2066 healthy children and 603 children with respiratory infections. Streptococcus pneumoniae and their DNA were detected in nasopharyngeal swabs by classical culture and molecular methods. Typing was carried out by molecular methods. On the territory of the Russian Federation, pneumococci belonging to the serotypes included in the 13-valent vaccine are being forced out of circulation and replaced by non-vaccine serotypes. Before the introduction of mass antipneumococcal vaccination (until 2015), the 13-valent conjugate vaccine covered from 66.2% to 92% of pneumococci, after the start of mass anti-pneumococcal vaccination in the period 2016-2018, coverage decreased to 57.3%. Between 2020 and 2022, coverage was less than 40%. The main “non-vaccine” serotypes/serogroups circulating in the Russian Federation are 15AF, 11AD, 23A, 9LN and 16F.